Stigma and Identity: A Phenomenological Study of LGBT+ Youth on Indonesian Social Media - Syam, Syahrianti; Iba, La (Socious Journal, 2025)
The development of social media has reconfigured the dynamics of identity formation and stigma reproduction for LGBT+ youth in the conservative Indonesian context. This study aims to examine how LGBT+ youth interpret their identities and confront stigma in digital spaces, using a qualitative approach based on literature studies and a phenomenological framework. Social media, on the one hand, provides an alternative space that enables the expression of gender and sexual identities through dynamic performative practices. However, on the other hand, digital platforms also become arenas for the reproduction of symbolic power that reinforce heteronormative norms through hate speech, negative labeling, and biased algorithmic moderation. In this situation, LGBT+ youth develop resistance strategies through the formation of online communities, social campaigns, and the production of affirmative narratives. This phenomenon reflects the importance of digital agency in the process of identity emancipation, while also revealing the dilemmas of visibility and security experienced by vulnerable groups. This analysis demonstrates that social media is a complex and transformative terrain of identity politics and emphasizes the need for more inclusive policy design and digital literacy. This study contributes to the academic literature by offering a deeper understanding of LGBT+ youth's subjectivities in navigating social stigma through digital spaces in contemporary Indonesian society.